The Taboo of Pleasure. A Traditionalist Critique of Freudian Individualistic Sexuality. - Jedliński, Marek (Sensus Historiae, 2024)
The aim of this paper is to analyse the traditionalist criticism of Freudianism. The Viennese psychoanalyst identified the factors that stigmatise sexual pleasure, namely shame, revulsion, and morality. The thesis is that taboos and traditions are transmitted from one generation to another. They shape traditional communities and challenge individual pleasure. It is concluded that traditionalism has a universal dimension, as it is present in both religious and Bolshevik traditionalism.